Legal Protection of Joint Property in Serial Marriage - Yuninda Dwi Kartika; Riza Zulfikar; Bambang Slamet (Rechtsvinding, 2026)
Nowadays, there are still many people in Indonesia who hold or carry out marriages that are legally legal but are not registered in the state. Marriages that are legally valid in religion but not registered in the state (sirri marriage or underhand marriage) raise various legal problems, one of which is regarding the legality of including the name of the spouse on the assets obtained during the marriage This is related to many problems, especially in the protection of the rights of women and children in legally valid marriages but not registered in the state. Meanwhile, the State has sought to protect the rights of Women and Children, one of which is the issuance of Law No: 1 of 1974 concerning Marriage and the Compilation of Islamic Law and stipulates that a valid marriage is a marriage that is carried out according to the laws of their respective religions and recorded in accordance with the applicable laws and regulations. Assets in marriage in Indonesia are divided into two main categories, namely inherited/personal property and joint property (gonogini). Based on Law No: 1 of 1974, all assets before marriage are inheritances, or gifts are the personal property of each and all assets obtained in marriage become joint property, unless there is a prenuptial agreement. In marriages that are religiously valid but not recorded in the state, it does not rule out the possibility of the birth of children and the emergence of property obtained in the marriage. However, in this case, in the event of divorce or breakup, the state cannot be present to protect the rights of women and children in terms of the division of property or the distribution of inheritance to property or assets obtained in a marriage that is legally religious but not recorded in the country. So that it causes many problems for families who are abandoned or the separation of marriages, the impact of which is felt by many people, especially women and children. This article examines in depth the legal position of marriage that is not recorded in the Indonesian legal system, the status of joint property in the marriage, as well as the technicaljuridical issues of including the name of the spouse in asset ownership documents such as land rights certificates, sale and purchase deeds, fiduciary deeds, and banking documents and examines the importance of providing legal awareness for the wider community, especially women, about the legal consequences or impacts of legal marriage religiously but not recorded in the state. Thus, it is hoped that the community will better understand and reduce religious legal marriages that are not recorded according to applicable laws and regulations, become legally and recorded marriages so that the state can be present to protect the rights of all its citizens, especially women and children.